Research of the is intense-deformed condition in a design of knot of fastening of a cutting plate using method of photo elasticity - A N Popikov; V A Rogov (RUDN Journal of Engineering Research, 2009)
On poljarizatsionno-optical models the is intense-deformed condition of knot of fastening of a cutting plate is studied. Fields of pressure depending on a material and geometry of the basic plate, arising are modelled at cutting in the field of contact of a cutting plate to a basic and basic plate with the cutter case.